Big pharma biopolitics: A critical study of vaccine trials in Indonesia - a legal review - Krisnayanto, Krisnayanto; Suryadi, Suryadi (Edelweiss Applied Science and Technology, 2025)
The globalization of pharmaceutical research has increasingly moved clinical trials to countries in the Global South, often raising serious concerns about ethics, legal oversight, and national sovereignty. This paper critically explores vaccine trials conducted in Indonesia by multinational pharmaceutical companies (commonly called Big Pharma) in collaboration with local institutions. Using a legal and geopolitical perspective, we examine how these trials reflect a broader system of biopower, where public health becomes intertwined with global market interests and strategic international agendas. By combining doctrinal legal analysis with critical discourse methods, our study finds that Indonesia’s regulatory framework lacks the strength and independence necessary to protect its citizens from potentially exploitative biomedical practices fully. We recommend a legal approach based on human rights, emphasizing health sovereignty and ethical accountability.